Solvent-free enantioselective conjugate addition and bioactivities of nitromethane to Chalcone containing pyridine. Issue 2 (12th January 2017) - Zhang, Guoping; Zhu, Chun; Liu, Dengyue; Pan, Jianke; Zhang, Jian; Hu, Deyu; Song, Baoan
Abstract: A series of chiral thioureas derived from quinine were tested as catalysts in the enantioselective Michael additions of nitromethane to α, β -unsaturated ketones containing pyridine. The best results were obtained with the bifunctional catalyst prepared from 3, 5-di(trifluoromethyl)-aniline under solvent-free conditions. This thiourea promoted the reaction with high enantioselectivities and chemical yields for aryl ketones. The origins of enantioselectivity were further investigated via experiment and computation. Meanwhile, the products from our reaction showed potent antibacterial activities against rice bacterial leaf blight, with the S -enantiomer performing much better than the R -enantiomer. Given the promising bioactivity of this class of molecules, our work is expected to offer important applications in developing future generations for drug design. Graphical abstract: